KINETICS OF ORGANIC MATTER DEGRADATION, MICROBIAL METHANE GENERATION, AND GAS HYDRATE FORMATION IN ANOXIC MARINE SEDIMENTS - Wallmann K.; Haeckel M.; Aloisi G.; Obzhirov A.; Pavlova G.; Tishchenko P. (My University, 2006)
Seven sediment cores were taken in the Sea of Okhotsk in a south-north transect along the slope of Sakhalin Island. The retrieved anoxic sediments and pore fluids were analyzed for particulate organic carbon (POC), total nitrogen, total sulfur, dissolved sulfate, sulfide, methane, ammonium, iodide, bromide, calcium, and total alkalinity. A novel method was developed to derive sedimentation rates from a steady-state nitrogen mass balance. Rates of organic matter degradation, sulfate reduction, methane turnover, and carbonate precipitation were derived from the data applying a steady-state transport-reaction model. A good fit to the data set was obtained using the following new rate law for organic matter degradation in anoxic sediments:RPOC = frac(KC, C (DIC) + C (CH4) + KC) · kx · POCThe rate of particulate organic carbon degradation (RPOC) was found to depend on the POC concentration, an age-dependent kinetic constant (kx) and the concentration of dissolved metabolites. Rates are inhibited at high dissolved inorganic carbon (DIC) and dissolved methane (CH4) concentrations. The best fit to the data was obtained applying an inhibition constant KC of 35 ± 5 mM. The modeling further showed that bromide and iodide are preferentially released during organic matter degradation in anoxic sediments. Carbonate precipitation is driven by the anaerobic oxidation of methane (AOM) and removes one third of the carbonate alkalinity generated via AOM. The new model of organic matter degradation was further tested and extended to simulate the accumulation of gas hydrates at Blake Ridge. A good fit to the available POC, total nitrogen, dissolved ammonium, bromide, iodide and sulfate data was obtained confirming that the new model can be used to simulate organic matter degradation and methane production over the entire hydrate stability zone (HSZ). The modeling revealed that most of the gas hydrates accumulating in Blake Ridge sediments are neither formed by organic matter degradation within the HSZ nor by dissolved methane transported to the surface by upward fluid flow but rather through the ascent of gas bubbles from deeper sediment layers. The model was further applied to predict rates of hydrate accumulation in Sakhalin slope sediments. It showed that only up to 0.3% of the pore space is occupied by gas hydrates formed via organic matter degradation within the HSZ. Gas bubble ascent may, however, significantly increase the total amount of hydrate in these deposits. © 2006 Elsevier Inc. All rights reserved.